2010
DOI: 10.1002/jso.21441
|View full text |Cite
|
Sign up to set email alerts
|

Medium to long‐term results after reconstruction of bone defects at the knee with tumor endoprostheses

Abstract: Regardless of achieving a low recurrence rate and satisfactory functional results, we found a high complication rate after implantation of a megaprosthesis. This was particularly evident for extraarticular resections and cemented fixation, which should be avoided when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 20 publications
5
56
0
6
Order By: Relevance
“…However, a radiolucent line between the extracortical bone and the shaft of the implant in the Noncollar Group clearly was evident in all cases except one. The importance of osteointegration at the shoulder has been recognized and some experimental studies have investigated methods to enhance extracortical bone formation, including the use of bone morphogenetic proteins [22] and stem cells [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, a radiolucent line between the extracortical bone and the shaft of the implant in the Noncollar Group clearly was evident in all cases except one. The importance of osteointegration at the shoulder has been recognized and some experimental studies have investigated methods to enhance extracortical bone formation, including the use of bone morphogenetic proteins [22] and stem cells [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative infection is an especially severe problem in patients with sarcoma as it contraindicates or retards postoperative chemotherapy and may have a negative impact on the prognosis in patients requiring such chemotherapy. Some studies have focused on perioperative infections [9,10,14,17,26] and perioperative antibiotic use [2,3,5,15,18,21,25,26,29,30] after tumor endoprosthetic reconstruction. However, appropriate antibiotic use for patients having tumor prosthetic surgery is unknown and remains controversial [5,7,15,18,21,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [9,10,14,17,26] have reported perioperative (early) infection rates after tumor endoprostheses from 2.6% to 7.4%. However, the criteria of early infection varied from infections occurring within 3 months [10,17], or within 6 months [14], to infections within 1 year after definitive surgery [9]. Without consideration of tumor types and surgical sites, the 1.9% (1/53) perioperative infection rate in our study is lower than the 7.4% early infection rate (within 3 months after surgery) reported in one study [26] with shorter duration of antibiotic use (2 days versus 8 days in our study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prosthetic reconstruction allows rapid restoration of mobility and weightbearing, but complications have been described in 25-92% of cases [2,3]. A 57% cumulative five-year survival for knee prostheses has been reported [4]. Stress shielding and prosthetic loosening remain major concerns and may require major revision surgery, resulting in further bone loss [5][6][7].…”
Section: Introductionmentioning
confidence: 99%